Arctic ice-ocean interactions in an 8-to-2 kilometer resolution global model - Elizabeth C. Fine; Julie L. McClean; Detelina P. Ivanova; Anthony P. Craig; Alan J. Wallcraft; Eric P. Chassignet; Elizabeth C. Hunke (Ocean Modelling, 2023)

A Review of Arctic Sea Ice Climate Predictability in Large-Scale Earth System Models - Marika Holland; Elizabeth Hunke (Oceanography, 2022)
We provide a high-level review of sea ice models used for climate studies and of the recent advances made with these models to understand sea ice predictability. Models currently in use for the Coupled Model Intercomparison Project and new developments coming online that will enable enhanced predictions are discussed. Previous work indicates that seasonal sea ice can be predicted based on mechanisms associated with long-lived ice thickness or ocean heat anomalies. On longer timescales, internal climate variability is an important source of uncertainty, although anthropogenic forcing is sizable, and studies suggest that anthropogenic signals have already emerged from internal climate noise. Using new analysis from the Multi-Model Large Ensemble, we show that while models differ in the magnitude and timing of predictable signals, many ice predictability characteristics are robust across multiple models. This includes the reemergence of predictable seasonal signals in ice area and the sizable uncertainty in predictions of ice-free Arctic timing associated with internal variability.

Should Sea-Ice Modeling Tools Designed for Climate Research Be Used for Short-Term Forecasting? - Elizabeth Hunke; Richard Allard; Philippe Blain; Ed Blockley; Daniel Feltham; Thierry Fichefet; Gilles Garric; Robert Grumbine; Jean-François Lemieux; Till Rasmussen; Mads Ribergaard; Andrew Roberts; et al. (Current Climate Change Reports, 2020)
In theory, the same sea-ice models could be used for both research and operations, but in practice, differences in scientific and software requirements and computational and human resources complicate the matter. Although sea-ice modeling tools developed for climate studies and other research applications produce output of interest to operational forecast users, such as ice motion, convergence, and internal ice pressure, the relevant spatial and temporal scales may not be sufficiently resolved. For instance, sea-ice research codes are typically run with horizontal resolution of more than 3 km, while mariners need information on scales less than 300 m. Certain sea-ice processes and coupled feedbacks that are critical to simulating the Earth system may not be relevant on these scales; and therefore, the most important model upgrades for improving sea-ice predictions might be made in the atmosphere and ocean components of coupled models or in their coupling mechanisms, rather than in the sea-ice model itself. This paper discusses some of the challenges in applying sea-ice modeling tools developed for research purposes for operational forecasting on short time scales, and highlights promising new directions in sea-ice modeling.